Hrip1 mediates rice cell wall fortification and phytoalexins elicitation to confer immunity against Magnaporthe oryzae - Ninkuu, Vincent; Yan, Jianpei; Zhang, Lin; Fu, Zhenchao; Yang, Tengfeng; Li, Shupeng; Li, Beibei; Duan, Jiaqi; Ren, Jie; Li, Guangyue; Yang, Xiufen; Zeng, Hongmei (Frontiers in Plant Science, 2022)
Abstract Magnaporthe oryzae is a potent fungus that adversely affects rice yield. Combinatorial techniques of prevention, toxic chemicals, and fungicide are used to remedy rice blast infection. We reported the role of Hrip1 in cell death elicitation and expression of systematic acquired resistance. In this study, transcriptome and metabolomic techniques were used to investigate the genomic basis of Hrip1 immunity induction against Magnaporthe oryzae in rice. Our results showed that Hrip1 induces cell wall thickening and phytoalexin elicitation to confer immunity to M. oryzae infection. Hrip1 activates key lignin biosynthetic genes and myeloblastosis transcription factors that act as molecular switches for lignin production. Lignin content analyzed by the thioglycolic acid method showed a 68.46% lignin accumulation in Hrip1-treated seedlings compared to the control groups. Further analysis of cell wall morphology using the transmission electron microscopy technique revealed over 100% cell wall robustness. Hrip1 also induced the expression of 24 diterpene synthases. These include class I and II terpene synthases, cytochrome P450 subfamilies (OsCYP76M and OsCYP71Z), and momilactones synthases. The relationship between the expression of these genes and metabolic elicitation was analyzed using ultra-performance liquid chromatography-tandem mass spectrometry. Enhanced amounts of momilactones A and B, oryzalactone, and phytocassane A and G were detected in the Hrip1-treated leaves. We also identified seven benzoxazinoid genes (BX1-BX7) that could improve rice immunity induction. Our findings show that Hrip1 confers dual immunity by leveraging lignin and phytoalexins for physical and chemical resistance. This study provides novel insights into the mechanisms underlying Hrip1-induced plant immunity.